Autonomous Mowing and Turf-Type Bermudagrass as Innovations for An Environment-Friendly Floor Management of a Vineyard in Coastal Tuscany - Simone Magni; Mino Sportelli; Nicola Grossi; Marco Volterrani; Alberto Minelli; Michel Pirchio; Marco Fontanelli; Christian Frasconi; Monica Gaetani; Luisa Martelloni; Andrea Peruzzi; Michele Raffaelli; et al. (Agriculture, 2020)
The establishment of permanent cover crops is becoming a common practice in vineyard floor management. Turfgrass science may provide species and techniques with a high potential for improving the sustainability of vineyard floor management. Based on this assumption, an experiment was carried out during 2018 and 2019 at the Donna Olimpia Vineyard, Bolgheri, Italy. The trial aimed at comparing an innovative floor management system based on a turf-type cultivar of bermudagrass mown with an autonomous mower with a conventional floor management system. Ground cover percentage, energy consumption, CO2 emissions, grapevine water status, leaf nitrogen content, fruit yield and must composition have been assessed in order to perform the comparison. The innovative vineyard floor management produced an almost complete ground cover (98%) at the end of the second growing season, with the resident species reduced to a small percentage (4%). Resident species growing under-trellis were efficiently controlled without herbicide applications. A lower primary energy consumption and a reduction in CO2 emissions were observed for the innovative management system compared to the conventional management system. Grapevine water status, leaf chlorophyll content, soil–plant analyses development (SPAD), fruit yields and must composition were similar between the different soil management systems. Based on results obtained in this trial, turf-type bermudagrass and innovative mowing machines may contribute to enhance the sustainability of vineyard floor management.